2002
DOI: 10.1103/physrevb.65.165432
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of surface plasmon polaritons on short-pitch metal gratings

Abstract: The dispersion of surface plasmon polaritons ͑SPPs͒ has been calculated for short-pitch metal gratings for various depths. For gratings with depths greater than their pitch very flat SPP bands are formed in the zero-order region of the spectrum which may be resonantly excited with radiation polarized with its electric field in the plane of incidence of the radiation, which also contains the grating vector. The dispersion curves of these modes evolve as deformations of the familiar shallow grating dispersion cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 14 publications
6
71
0
Order By: Relevance
“…Figure 3 Clearly, the two reflection minima are adjacent harmonics of the fundamental cavity mode resonance that exists in the grooves of the structure when the wires are optically thick and the grooves are narrow. Furthermore, examining the dependence of this family of modes on the grating height, and examining their dispersion diagrams as the height is varied, shows that they evolve from normal surface plasmon modes and, subsequently, they behave in exactly the same way as the cavity modes discussed in a similar investigation into surface relief gratings with a Gaussian cross-section [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 Clearly, the two reflection minima are adjacent harmonics of the fundamental cavity mode resonance that exists in the grooves of the structure when the wires are optically thick and the grooves are narrow. Furthermore, examining the dependence of this family of modes on the grating height, and examining their dispersion diagrams as the height is varied, shows that they evolve from normal surface plasmon modes and, subsequently, they behave in exactly the same way as the cavity modes discussed in a similar investigation into surface relief gratings with a Gaussian cross-section [6].…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been shown that surface plasmons may be excited in the zero-order region of the spectrum, as they evolve to form cavity modes in the grooves of the structure [4][5][6]. Further work has also examined the nature of these cavity modes on gratings whose ridges are sufficiently narrow that the surface plasmon modes on each vertical surface may also interact through the metal ridges, as well as across the grooves [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Through modeling it has also been shown that it is possible to excite these flat-banded SPP's on zero-order gratings where SPP excitation would not be possible on lower aspect ratio structures. [7][8][9] However, the resonant absorption bands are found to be very broad and shallow. These flatbanded SPP modes have antisymmetric charge distributions on either side of the grating grooves, the fields of which then couple together to produce a highly localized self-coupled SPP.…”
Section: Introductionmentioning
confidence: 98%
“…The splitting is highly dependent on the grating geometry, more specifically on the fillfactor FF and triangle height H. The effects of the two geometrical parameters can be traced by examining the Fourier expansion of the grating profile [24]. It can be shown that at FF=1…”
Section: A Using Spp Modesmentioning
confidence: 99%